The Relationship between Knowledge of Oral Health Maintenance with the Incidence of Gingivitis in Traders (JURNAL PROTEKSI KESEHATAN, 2024)
Gingivitis is a periodontal disease involving the gingival tissue, caused by bacterial invasion. The emergence of gingivitis problems in society can be caused by individual behavioral factors that neglect oral hygiene due to lack of individual knowledge about the importance of oral health maintenance. This study aims to see the relationship between knowledge of oral health maintenance and the incidence of gingivitis in traders at Tanjungsari Square, Tanjungsari Village, Sumedang Regency. This analytic study with a cross sectional design took samples with purposive sampling technique as many as 31 respondents. Data were collected through questionnaires and modified gingival index (MGI) examination. The results showed that as many as 13 (41.9%) respondents still had a level of knowledge in the lack category and as many as 12 (38.7%) respondents still had gingivitis with moderate inflammation. The Spearman test obtained a p-value of 0.037